Current evidence of gut microbiota dysbiosis and its role in atrial fibrillation and cardiovascular diseases - Szwarkowska, Maria; Sobieszek, Kamil A.; Bartus, Krzysztof; Sadowski, Jerzy (Folia Medica Cracoviensia, 2026)
The human gut microbiota has emerged recently as an important regulator of cardiovascular physiology through its effects on metabolism, immune signaling, and systemic inflammation. Increasing evidence suggests that alterations in intestinal microbial composition (dysbiosis) may contribute to the development and progression of atrial fibrillation (AF). This review summarizes current evidence on gut microbiota alterations, microbiota-derived metabolites, and their mechanistic links to atrial fibrillation pathogenesis and potential therapeutic strategies. Patients with AF demonstrate reduced microbial diversity and characteristic shifts in bacterial taxa, including depletion of short-chain fatty acid–producing bacteria and enrichment of potentially pro-inflammatory microorganisms. Gut microbiota–derived metabolites appear to play a key role in mediating these effects. Trimethylamine N-oxide (TMAO), lipopolysaccharide (LPS), and phenylacetylglutamine (PAGln) promote oxidative stress, endothelial dysfunction, and activation of inflammatory pathways such as NF-κB and the NLRP3 inflammasome, leading to atrial fibrosis, electrical remodeling, and increased arrhythmogenic susceptibility. In contrast, short-chain fatty acids exert anti-inflammatory and cardioprotective effects that may stabilize cardiac electrophysiology. Importantly, the relationship between gut microbiota and atrial fibrillation appears to be bidirectional, as cardiovascular disease itself may influence intestinal barrier integrity and microbial composition. Understanding the gut–heart axis may open new perspectives for risk stratification and therapeutic strategies, including dietary interventions and microbiome- targeted therapies. Further clinical studies are required to determine whether modulation of the gut microbiota can effectively prevent or modify the course of atrial fibrillation.